2017
DOI: 10.1016/j.nut.2017.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Serum vitamin D and change in lipid levels over 5 y: The Atherosclerosis Risk in Communities study

Abstract: Background 25-hydroxyvitamin D [25(OH)D] deficiency is associated with increased cardiovascular disease risk, perhaps mediated through dyslipidemia. Deficient 25(OH)D is cross-sectionally associated with dyslipidemia, but little is known about longitudinal lipid changes. Our objective was to determine the association of 25(OH)D deficiency with longitudinal lipid changes and risk of incident dyslipidemia. Research Methods This is a longitudinal community-based study of 13,039 ARIC participants who had 25(OH)D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 47 publications
3
20
1
Order By: Relevance
“…On the other hand, no effect has been observed on the levels of total cholesterol, even if recent observations suggest a role of vitamin D in modulating HDL-cholesterol also. 23 The mechanism by which vitamin D exerts its beneficial effect is incompletely known, although oxidative stress leading to IR has been documented in hepatic cell lines with vitamin D-induced deficiency. 24 Both histological analysis and staining with Oil Red O showed that WD leads to severe liver steatosis associated with altered hepatocyte structure.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, no effect has been observed on the levels of total cholesterol, even if recent observations suggest a role of vitamin D in modulating HDL-cholesterol also. 23 The mechanism by which vitamin D exerts its beneficial effect is incompletely known, although oxidative stress leading to IR has been documented in hepatic cell lines with vitamin D-induced deficiency. 24 Both histological analysis and staining with Oil Red O showed that WD leads to severe liver steatosis associated with altered hepatocyte structure.…”
Section: Discussionmentioning
confidence: 99%
“…The primary role of vitamin D is the mineralization of bone by regulating osteoblast activity and facilitating the absorption of calcium and phosphorus from the intestines and calcium from the kidneys via its active metabolite 1,25-dihydroxyvitamin D. 5 , 6 However, many studies have shown an association between vitamin D deficiency and chronic diseases including cardiovascular disease and its risk factors including dyslipidemia. 5 - 9 In a nationally representative sample of children aged 1 to 21 years, in the National Health and Nutrition Examination Survey of 2001 to 2004, the authors concluded that vitamin D deficiency is common in the general US pediatric population and is associated with adverse cardiovascular risks. 10 In a cross-sectional study of children aged 1 to 5 years from Canada, 25(OH)D levels were inversely associated with circulating lipids in early childhood, suggesting that vitamin D exposure in early life may be a modifiable risk for cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…Further carefully controlled experimental study is needed to better understand the observation. Low serum 25(OH)D concentrations have been associated with dyslipidemia, indicated as increased serum levels of TC, LDL-c and TG, and low levels of HDL-c, which could possibly explain the relation with diabetes and cardiovascular diseases [42,43]. Ford et al [44] in their analysis of the third National Health and Nutrition Examination Survey (NHANES) revealed inverse associations between serum 25(OH)D concentrations and TG in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%